Perceptions towards the prescribing of antibiotics by pharmacists and the use of antibiotics in primary care in South Africa - Truter, Ilse; Knoesen, Brent C (The Journal of Infection in Developing Countries, 2018)
Introduction: Antibiotics deserve their place a powerful pillar in modern medical care, but the development of antibiotic resistance is emerging faster than the availability of new antibiotics. This poses a major threat to public health. The primary aim was to determine the perceptions towards the prescribing of antibiotics by pharmacists and the use of antibiotics in primary care in Nelson Mandela Bay, South Africa. Methodology: A questionnaire survey was conducted under community pharmacists during 2014. Purposive sampling was used. Results: Eighty percent of pharmacists were of the opinion that antibiotics are overprescribed. Amoxicillin, or the combination of amoxicillin with clavulanic acid, was indicated by 87.5% of respondents as the most often dispensed in their pharmacies, with ciprofloxacin, clarithromycin and azithromycin also commonly dispensed. One specific trade name product was mentioned by 43.8% of respondents as the antibiotic product they most often dispense. The most common diagnoses for which antibiotics were dispensed were upper respiratory tract infections and sinusitis. On average, more females (60.0%) were dispensed antibiotics. Most antibiotics were dispensed to adults (44.4%) and children (23.1%). On the question whether respondents were of the opinion that pharmacists should prescribe antibiotics, 50.0% indicated that they do not agree and 31.3% agreed. The main reason was because pharmacists are not qualified to diagnose. However, with further training they should be able to diagnose minor ailments and counsel patients. Conclusions: Pharmacists had mixed opinions on whether they should be able to prescribe antibiotics. Most pharmacists were of the opinion that antibiotics are overprescribed.